A study on the user evaluation for an RDA-based Korean bibliography retrieval system. Issue 3 (21st September 2015) - Do, Seulki; Oh, Sam G.; Lee, Sungin
Abstract : Purpose: – The purpose of this paper is to validate the usefulness of resource description and access (RDA) from user perspectives by implementing an RDA-based bibliographic retrieval system, and comparing it against two retrieval systems. Design/methodology/approach: – Surveys and interviews were conducted to gather responses from 20 subjects who used the systems. Usability was measured according to the following metrics: search usefulness from search process and results; search efficiency, measured in time and the number of steps involved; general satisfaction for search results and process, and for information need; satisfaction for search functionalities, with five sub-measures (usability of functions of search tool, appropriateness of search results, usability of additional information, usability of associative relations, and appropriateness of search categories); and system convenience in terms of understandability and ease. Findings: – The survey results indicate that all but the satisfaction for appropriateness of search categories showed significant differences between the systems. The interviews show that the RDA system received from the subjects a more positive evaluation compared to the counterpart systems, in search usefulness, search efficiency, general search satisfaction, satisfaction for search functionalities. Practical implications: – Though a few organizations such as the Library of Congress in the USA have implemented RDA, no such endeavors have been undertaken in the context of Korean bibliography, and especially for the systematic validation of usability of such a system from user perspectives. Originality/value: – This is the first published study that validates the usefulness perceived by users of RDA in the context of Korean bibliography.